Performance of Malaysian Financial Firms: An Intellectual Capital Perspective Using MVAIC Model - Mohammad, Hapsah S; Bujang, Imbarine (Asian Economic and Financial Review, 2019)
This study examined the influence of intellectual capital on Malaysian financial firms from two perspectives, performance of intellectual capital and impact of intellectual capital on financial performance. The data used were collected from the audited annual reports of 21 financial firms listed in the finance sector of Bursa Malaysia. The sample period was from 2011 to 2015 and the number of observations for this analysis was 105. Intellectual capital was measured using the modified value-added intellectual coefficient (MVAIC) model and financial performance was proxied by the return on asset (ROA). The findings suggested a strong association between MVAIC and ROA. CEE, HCE and SCE made significant and positive contributions towards financial performance. As for RCE, the findings revealed a positive but insignificant relationship with ROA. On the performance of intellectual capital, the HCE contributed approximately 82% to MVAIC followed by SCE 16%, RCE 1% and CEE 1%. Thus, the value creation capability of Malaysian financial firms is directly attributable to the HCE of the firms. The main limitations of the study were no control for firm-specific variables such as firm-size, and that the level of risk, firms’ complexity and structural capital were not segregated into its components namely innovation capital and process capital to identify which was more dominant in creating value. Financial firms may use the results to address the factors affecting intellectual capital performance in order to maximize value creation capability. Education institutions need to collaborate with the finance industry to increase the relevance of their educational mission and to stimulate new directions in the education industry.